Social Preferences: Fundamental Characteristics and Economic Consequences - Fehr, Ernst; Charness, Gary (Journal of Economic Literature, 2025)
We review the vast literature on social preferences by assessing what is known about their fundamental properties, their distribution in the broader population, and their consequences for important economic and political behaviors. We provide, in particular, an overview of the empirical characteristics of distributional preferences and how they are affected by merit, luck, and concerns for equality of opportunity. In addition, we discuss the evidence for reciprocity and guilt aversion and assess the empirical relevance of self-image and social image concerns in prosocial behaviors. The overall evidence indicates that a large majority of individuals have some sort of social preferences, while purely self-interested subjects are a minority. We also document converging insights from the lab and the field on the impact of wage inequality on work morale, employees’ resistance to wage cuts, and the role of social preferences for cooperation and collective action, distributive politics, and individuals’ selection into different occupations. (JEL D63, D71, D72, D86, H23, J53)